6x+12+2x+60=90

Simple and best practice solution for 6x+12+2x+60=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+12+2x+60=90 equation:


Simplifying
6x + 12 + 2x + 60 = 90

Reorder the terms:
12 + 60 + 6x + 2x = 90

Combine like terms: 12 + 60 = 72
72 + 6x + 2x = 90

Combine like terms: 6x + 2x = 8x
72 + 8x = 90

Solving
72 + 8x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-72' to each side of the equation.
72 + -72 + 8x = 90 + -72

Combine like terms: 72 + -72 = 0
0 + 8x = 90 + -72
8x = 90 + -72

Combine like terms: 90 + -72 = 18
8x = 18

Divide each side by '8'.
x = 2.25

Simplifying
x = 2.25

See similar equations:

| -12.7+-4.4=x | | K+(-6)=4 | | -3x-3+9x+7-x=29 | | -3x-3+9x+7x-x=29 | | (6x-w)(7x+w)= | | 14z+11-5z= | | 2+(-9)=f-4 | | 2mp+3np+2mr+3nr= | | 3n-4+6n+2=6+4n+2 | | (-5)-(-8)=g+7 | | 4x+4=19-x | | (-37)=c+(-14) | | 6a-2-4a=3a+4+5a | | 0=-5n-2n-2n | | (-5)=b+(-11) | | -8x^2-8x+160=0 | | A-5=(-8) | | 3x*26= | | 6(x-1)+2=6x-2 | | -7y=-10-8y | | 0=-4.9t^2+.686t | | J+(-3)=4 | | 7j+4=5j | | -5x-15=-20 | | 9y=9+10y | | -12+8+5=36 | | 2x+34x^2-322=0 | | 3+(-7)=f-3 | | 3y+9-8y+6-6=-5y-12 | | -12+3x=-6 | | 9n=-117 | | 3x+9-8x+6-6=-5x-12 |

Equations solver categories